Artificial Ureter in Patients with Extensive Ureteral Damage - Yazdani, Mohammad; Javid, Amir; Mohammadi Sichani, Mehrdad; Gharaati, Mohammad Reza; Yazdani, Emad (Urology Journal, 2017)
Purpose: loss of significant lengths of ureter when substitution with bowel or bladder fails is a disaster in urology. This study is conducted to evaluate the results of subcutaneous nephron-vesical bypass (SNVB) in ureteral damage of different etiologies. Materials and Methods: Seventeen SNVB were employed in patients with ureteral injuries. We employed a device consisted of an internal silicone tube covered by a coiled PTFE tube to replace the ureter. This is called artificial ureter (AU). Proximal end of the AU was introduced in the kidney percutaneously, the tube was passed through a subcutaneous tunnel, while the distal end was inserted in the bladder through a small suprapubic incision. Results: Follow-up ranged from six months to ten years. We removed the prosthetic ureter in one patient due to gross hematuria two months after insertion. One of the patients was reoperated two days after the procedure because of urinary leakage. In all other patients, the procedure was safe and effective. Conclusion: Subcutaneous nephron-vesical bypass is a safe and appealing alternative to a nephrostomy tube. This is a permanent device with no need for exchange. The technique can be applied in ureteral injuries due to various causes.